Cherokee Meadows Road Association - miscellaneous - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2014)
Located in: Fort Collins office files. Cherokee Meadows Road Association (CMRA) miscellaneous records related to Colorado State Forest Service (CSFS) State Fire Assistance (SFA) and Wildland Urban Interface (WUI) grant. Includes: program payment request with cost-share program reimbursement request and worksheet; accomplishments report; notes; printouts of Firewise Communities USA/Recognition program - Firewise webpage with annotations with related mapping and troubleshooting documents; printouts of email related to Firewise Virtual workshops; photocopies of Firewise Communities homeowner information; Landowner Assistance Programs (LOA) cost documentation log sheets; invoices; receipts; financial statements; home wildfire assessment and mitigation guide report; CMRA/LFPD (Livermore Fire Protection District) defensible space evaluation; photocopies of annotated maps; photographic prints; and 34 digital photographs of mitigation (thinning, stacking, and clearance) of slash pine trees before and after.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado